Stakehold Engagement Plan (SEP)-AICCRA Additional Financing (P181150) - International Center for Tropical Agriculture (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This Stakeholder Engagement Plan (SEP) has been updated for the Additional Financing (AF) of the Accelerating Impact of CGIAR Climate Research for Africa (AICCRA) project (P181150). This updated SEP will be used for the Parent Project (P173398) and the AF (P181150). It has been prepared to define information disclosure, establish stakeholder engagement measures, and provide a grievance mechanism (GM). The SEP outlines how, when, and ways in which the project team will inform, communicate, and consult with stakeholders, including vulnerable groups, and a mechanism by which people can raise concerns, provide feedback, or make complaints about the AICCRA-AF and any activities related to the project. The SEP is prepared in accordance with the Environmental and Social Standard 10 (ESS-10) on Stakeholder Engagement and Information Disclosure of the World Bank’s Environmental and Social Framework (ESF).